Antropólogo Chirif Alberto - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: La fotografía muestra al antropólogo peruano Alberto Chirif, quien a dedicado su vida a la Amazonía y sus pueblos indígenas. Su obra y diversos intereses están documentados en diversos estudios y libros sobre derechos indígenas, territorio, memoria e historia, diccionarios regionales, cocina indígena y literatura amazónica. Testigo extraordinario de la historia de la Amazonía y del Perú. Alberto siempre mostró hacer cambios que marcarían el rumbos del país, con la antropología amazónica y los movimientos indígenas amazónicos.
ENGLISH: The photograph shows Peruvian anthropologist Alberto Chirif, who has dedicated his life to the Amazon and its indigenous peoples. His work and diverse interests are documented in several studies and books on indigenous rights, territory, memory and history, regional dictionaries, indigenous cuisine and Amazonian literature. Extraordinary witness of the history of the Amazon and Peru. Alberto always showed to make changes that would mark the course of the country, with the Amazonian anthropology and the Amazonian indigenous movements.

SPANISH: La fotografía muestra al antropólogo peruano Alberto Chirif, quien a dedicado su vida a la Amazonía y sus pueblos indígenas. Su obra y diversos intereses están documentados en diversos estudios y libros sobre derechos indígenas, territorio, memoria e historia, diccionarios regionales, cocina indígena y literatura amazónica. Testigo extraordinario de la historia de la Amazonía y del Perú. Alberto siempre mostró hacer cambios que marcarían el rumbos del país, con la antropología amazónica y los movimientos indígenas amazónicos.
ENGLISH: The photograph shows Peruvian anthropologist Alberto Chirif, who has dedicated his life to the Amazon and its indigenous peoples. His work and diverse interests are documented in several studies and books on indigenous rights, territory, memory and history, regional dictionaries, indigenous cuisine and Amazonian literature. Extraordinary witness of the history of the Amazon and Peru. Alberto always showed to make changes that would mark the course of the country, with the Amazonian anthropology and the Amazonian indigenous movements.
Anthropologist Chirif Alberto
Keywords: Iquitos (Perú)|~|Actividades culturales|~|Perú|~|Perú--Cultura Amazónica|~|Perú--Personajes Religiosos